Strategies for Prevention: Mental Health Nurse Burnout and Stress - Sadiku(Alterziu), Violeta (European Journal of Multidisciplinary Studies, 2016)
The aim of this critical review was to identify prevention strategies that may be effective in the reduction of stress and burnout among mental health nurses. Diminished staff wellbeing, due to high levels of stress and burnout, has significant consequences at both the individual and the service level. Therefore, identifying effective prevention strategies may be beneficial in raising recruitment of mental health nurses, in prolonging retention, and may also have a positive impact on patient care. A search of the literature was undertaken utilising selected systematic review techniques, which identified seven articles as suitable for review. The results of the review found that three main prevention strategies were being utilised: clinical supervision, psychosocial intervention and social support. While all these strategies had the aim of minimising or preventing stress and/or burnout, they were all somewhat different in their focus and in their outcome measures. This factor, coupled with the paucity of high quality randomised intervention studies, makes it difficult to draw definitive conclusions concerning which intervention is most effective. The best currently available evidence suggests that prolonged clinical supervision is probably the best of the three options for the reduction of stress and burnout among mental health nurses, given the lack of high quality evidence and the magnitude and potential impact of this problem